Аналіз причин порушення функціонального стану нирок у хворих на вперше діагностований туберкульоз легень (огляд літератури, спостереження авторів) = Analysis of the causes of violations of the functional state of kidneys in patients which for the first time diagnosed of pulmonary TB (literature review, observation of the authors) = Анализ причин нарушения функционального состояния почек у больных с впервые диагностированным туберкулезом легких (обзор литературы, наблюдения авторов) - Matsegora, N. A.; Beseda, Ya. V.; Leonenko-Brodetska, O. M.; Lekan, O. Ya. (Journal of Education, Health and Sport, 2017)
Matsegora N. A., Beseda Ya. V., Leonenko-Brodetska O. M., Lekan O. Ya. Аналіз причин порушення функціонального стану нирок у хворих на вперше діагностований туберкульоз легень (огляд літератури, спостереження авторів) = Analysis of the causes of violations of the functional state of kidneys in patients which for the first time diagnosed of pulmonary TB (literature review, observation of the authors) = Анализ причин нарушения функционального состояния почек у больных с впервые диагностированным туберкулезом легких (обзор литературы, наблюдения авторов). 2016;6(11):657-679. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.209922 http://ojs.ukw.edu.pl/index.php/johs/article/view/4082 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 30.11.2016. АНАЛІЗ ПРИЧИН ПОРУШЕННЯ ФУНКЦІОНАЛЬНОГО СТАНУ НИРОК У ХВОРИХ НА ВПЕРШЕ ДІАГНОСТОВАНИЙ ТУБЕРКУЛЬОЗ ЛЕГЕНЬ (огляд літератури, спостереження авторів) Н. А. Мацегора, Я. В. Беседа, О. М. Леоненко-Бродецька, О. Я. Лекан Одеський національний медичний університет ANALYSIS OF THE CAUSES OF VIOLATIONS OF THE FUNCTIONAL STATE OF KIDNEYS IN PATIENTS WHICH FOR THE FIRST TIME DIAGNOSED OF PULMONARY TB (literature review, observation of the authors) N. A. Matsegora, Ya. V. Beseda, O. M. Leonenko-Brodetska, O. Ya. Lekan Odessa National Medical University Summary On the basis of review of literature, it is shown that forming of functional violations of organs of the system of detoxication and elimination for the patients for the first time diagnosed of pulmonary tuberculosis results in a necessity to diminish the dose of preparations, and in a number of cases, to interrupt setting of tuberculate antibiotics, that not only reduces quality of treatment but also results in forming of drug-resistant forms of tuberculosis. We are inspect 154 patients with for the first time diagnosed of pulmonary tuberculosis that acted on treatment in an active phase in theOdessaregional clinical tubercular hospital in 2011-2015. On a background the course of specific tuberculate antibiotics therapy was differentiated appointed patients L-arginine and silibinin depending on the level of microalbuminuria. It allowed to warn forming of proof disorders from the side of buds and liver, created possibility of realization of complete adequate antibacterial course of antiphthisic etiotropic therapy, to improve quality treatment of patients tuberculosis, bring down frequency of cases of interruptions in treatment, as one of leading reasons of forming of resistant forms of tuberculosis. Key words: for the first time diagnosed of pulmonary TB, microalbuminuria, organs of detoxification and elimination. АНАЛИЗ ПРИЧИН НАРУШЕНИЯ ФУНКЦИОНАЛЬНОГО СОСТОЯНИЯ ПОЧЕК У БОЛЬНЫХ С ВПЕРВЫЕ ДИАГНОСТИРОВАННЫМ ТУБЕРКУЛЕЗОМ ЛЕГКИХ (обзор литературы, наблюдения авторов) Н. А. Мацегора, Я. В. Беседа, О. М. Леоненко-Бродецкая, О. Я. Лекан Одесский национальный медицинский университет Резюме На основании обзора литературы показано, что формирование функциональных нарушений органов системы детоксикации и элиминации у больных ВДТБ легких приводит к необходимости уменьшать дозу препаратов, а в ряде случаев, прерывать назначение противотуберкулёзных антибиотиков, что не только снижает качество лечения, но и приводит к формированию химиорезистентных форм туберкулёза. Нами обследовано 154 больных с ВДТБ легких, которые поступали на лечение в активной фазе в Одесскую областную клиническую туберкулезную больницу в 2011-2015 годах. Пациенты находились в возрасте от 23 до 60 лет; преобладали мужчины (65,6%). На фоне курса специфической антибактериальной противотуберкулезной терапии больным дифференцированно назначались цитопротекторы L-аргинин и силибинин в зависимости от уровня микроальбуминурии. Это позволило предупредить формирование стойких расстройств со стороны почек и печени, создало возможность проведения полного адекватного антибактериального курса противотуберкулезной этиотропной терапии, повысить качество лечения больных туберкулезом, снизить частоту случаев перерывов в лечении, как одну из ведущих причин формирования резистентных форм туберкулёза. Ключевые слова: впервые диагностированный туберкулез легких, микроальбуминурия, органы детоксикации и элиминации.